COMMUNICATION PATTERNS IN MATAHARIKITA.CO VIRTUAL COMMUNITY BATCH 11 IN BUILDING SOLIDARITY - Pertiwi, Cholidah Astri Astri; Alfiana, Tiffani Iqlima; Farida, Nuke (Universitas Gunadarma, 2025)
This study aims to determine the communication patterns in the Mataharikita.co community batch 11 in building solidarity between members and between members and administrators. The research method used is a descriptive qualitative research method and using a constructivist paradigm. Data collection techniques used in the form of in-depth interviews with members and administrators in the Mataharikita.co, observation, and documentation. The theory used is the Symbolic Interactionism theory. The results of the study show that the communication pattern model that occurs in the Mataharikita.co batch 11 is a pattern of all channels or what is known as a star pattern that involves all members and administrators in communicating, thus encouraging a sense of family as a whole that can help build solidarity in the Mataharikita.co. An open communication pattern not only facilitates the exchange of information, but also strengthens mutual trust, responsibility, respect between members and administrators and togetherness between each other. Thus, this communication pattern plays an important role in creating a supportive and mutually reinforcing environment, making Mataharikita.co a place that is not only productive, but also full of togetherness and concern among its members.